2019
DOI: 10.1029/2018jd029073
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Controls on Observed Daytime Ozone Deposition Velocity Over Northeastern U.S. Forests During Summer

Abstract: Spatiotemporal variability in ozone dry deposition is often overlooked despite its implications for interpreting and modeling tropospheric ozone concentrations accurately. Understanding the influences of stomatal versus nonstomatal deposition processes on ozone deposition velocity is important for attributing observed changes in the ozone depositional sink and associated damage to ecosystems. Here, we aim to identify the stomatal versus nonstomatal deposition processes driving observed variability in ozone dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 122 publications
1
47
0
Order By: Relevance
“…Our modeling analysis, as supported by multiple observational data sets, indicates that limitation in stomatal conductance due to soil moisture deficits (as opposed to LAI changes) is the primary driver of V d,O3 variability during large‐scale drought events. On basis of data over one forest site, Clifton et al () notice enhanced non‐stomatal O 3 deposition in dry years associated with greater soil uptake; this effect is unlikely to influence observed V d,O3 variability during sub‐continental to continental scale drought events.…”
Section: Conclusion and Recommendationsmentioning
confidence: 98%
“…Our modeling analysis, as supported by multiple observational data sets, indicates that limitation in stomatal conductance due to soil moisture deficits (as opposed to LAI changes) is the primary driver of V d,O3 variability during large‐scale drought events. On basis of data over one forest site, Clifton et al () notice enhanced non‐stomatal O 3 deposition in dry years associated with greater soil uptake; this effect is unlikely to influence observed V d,O3 variability during sub‐continental to continental scale drought events.…”
Section: Conclusion and Recommendationsmentioning
confidence: 98%
“…Several field studies report increases in inferred nonstomatal uptake over vegetation with relative humidity, providing evidence that aqueous surface chemistry on leaves may be important at ecosystem scales (Altimir et al, 2006;Clifton et al, 2019;Lamaud et al, 2009;Q. Li, Gabay et al, 2018;Neirynck & Verstraeten, 2018;Rannik et al, 2012;L.…”
Section: Leaf Cuticles 421 Controls On Ozone Dry Deposition To Leamentioning
confidence: 99%
“…While there are fairly consistent increases in v d over vegetation after rain and dew across field studies (Table 2), whether observed responses truly indicate changes in cuticular uptake remains an open question. For example, there may be changes in g s after rain (e.g., Clifton et al, 2019) or emissions of highly reactive species that influence the observed ozone flux (e.g., Altimir et al, 2006;Clifton et al, 2019;Turnipseed et al, 2009).…”
Section: Leaf Cuticles 421 Controls On Ozone Dry Deposition To Leamentioning
confidence: 99%
See 2 more Smart Citations